Determinants of shisha use among secondary school students in Sudan - Othman, Mohammed (BMC Public Health, 2019)
BACKGROUND: Shisha smoking has re-emerged in the Middle East in the last two decades and has spread rapidly in these communities. Information about shisha smoking in adolescents in Sudan is deficient. Hence, the aim of this study is to estimate the prevalence of shisha smoking among adolescents and determine the associated factors. METHODS: This study is a school based cross sectional study among secondary school students in Khartoum State - Sudan that targets both male and female students aged 14–17 years. A total of 3387 students from 29 public and private schools were selected by multi stage random sampling. The participants completed an anonymous self-administered questionnaire which was based on Arabic version of the Global Youth Tobacco Survey (GYTS). RESULTS: The response rate was 100% in schools and among participants, 57.3% were females and 51.6% were from public schools. The overall prevalence of those who had ever smoked shisha was 13.4%, and among male students the prevalence was 16.8%, while it was 10.9% in females. The associated factors were poor academic performance OR 2.90 CI 95% (1.21–6.94), friends smoking shisha OR 2.39 CI 95% (1.65–3.45), friends smoking cigarettes OR 2.76 CI 95% (1.90–4.01), peer pressure to smoke shisha OR 13.76 CI 95% (7.86–24.07) and unexpectedly restriction of selling shisha to minors OR 2.21 CI 95% (1.28–3.82). CONCLUSION: The prevalence of those who had ever smoked shisha is among the lowest in Middle East region; therefore, regular surveillance system is needed. A well-structured peer based comprehensive tobacco control programmes that are supported by strict and rigorous anti-tobacco regulations which control both commercial and social resources of tobacco are needed to contain this issue among adolescents.